2019
DOI: 10.1016/j.ejvs.2019.03.019
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Post-EVAR Graft Limb Kinking in EVAR Limb Occlusion: Aetiology, Early Diagnosis, and Management

Abstract: The aim of this study was to review preventive and treatment management of one of the most common complications of endovascular aneurysm repair, which surprisingly, is little described in the literature. This study aimed to objectively identify high risk patients for kinking and make recommendations for intra-operative diagnosis and management, as well as management of limb occlusion.Objective/background: Endograft limb occlusion is a potential complication of endovascular aneurysm repair (EVAR), being one of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 51 publications
2
17
2
Order By: Relevance
“…Extension to EIA was a predictor for occlusion reported in many studies. 6,8,9,13 In our study, there were also more extensions to the EIA in occluded limbs (27.3%) than in patent limbs (9.4%), however, not statistically significant (P .108).…”
Section: Risk Factors For Stentgraft Limb Occlusioncontrasting
confidence: 56%
See 3 more Smart Citations
“…Extension to EIA was a predictor for occlusion reported in many studies. 6,8,9,13 In our study, there were also more extensions to the EIA in occluded limbs (27.3%) than in patent limbs (9.4%), however, not statistically significant (P .108).…”
Section: Risk Factors For Stentgraft Limb Occlusioncontrasting
confidence: 56%
“…This is in contrast to our study, in which distal aortic diameter was larger in occluded limbs (3.3 ± 1.1 cm) than in patent limbs (2.7 ± .8 cm), however, not statistically significant (p .312). Several studies demonstrated iliac artery tortuosity and calcification as risk factors for SLO; 6,11,12 in our study, there were no major differences. Faure et al 8 noted that if the diameter of the external iliac artery (EIA) was ≤1.0 cm, there was a higher risk of occlusion (P .001).…”
Section: Risk Factors For Stentgraft Limb Occlusionsupporting
confidence: 54%
See 2 more Smart Citations
“…Usually, the kinking of an AAA EVAR stent graft will occur at the level of the iliac artery limbs, with incidence of 1.5%, and contributes to lower extremity occlusion. 5 In the present case report, however, we have addressed a unique complication of AAA EVAR stent graft kinking at the level of the mid-body, which led to acute occlusion of the stent graft and bilateral iliac arteries. The graft in the present patient seemed to have migrated >5 mm from its original position, meeting the definition of stent displacement.…”
Section: Discussionmentioning
confidence: 90%